Did quality of life for older cancer survivors improve with the turn of the century in the United States?. Issue 1 (January 2021) - Mahal, Amandeep R.; Cramer, Laura D.; Wang, Elyn H.; Wang, Shiyi; Davidoff, Amy J.; Gross, Cary P.; Yu, James B.
Abstract: Objectives: Although survival after a cancer diagnosis has improved considerably over the past 20 years, little is known about trends in health-related quality-of-life (HRQOL) for older prostate, breast, and lung cancer survivors. Methods: Using a population-based registry with longitudinal patient reported outcomes (the National Cancer Institute Surveillance, Epidemiology and End Results database linked to Medicare Health Outcomes Survey), we analyzed Medicare Advantage patients diagnosed with cancer during 1998–2011, who completed surveys regarding HRQOL through 2013. 'Early Era' patients were treated during 1998–2003; 'Late Era' patients were treated during 2006–2011. After propensity score matching, post-diagnosis changes in health utility (HU), Physical Component Summary (PCS) and Mental Component Summary (MCS) scores were calculated and compared between the two eras. Result: We identified 208 older patients with prostate, 276 with breast and 76 with lung cancer who were treated in the 'Early Era' and matched to equal numbers in the 'Late Era'. Mean age of patients in early and late era was 72 and 73 years, respectively. The mean post-diagnosis decline in health utility for patients treated in the 'Late Era' was not significantly different from the 'Early Era' for any cancer (Prostate [early vs. late]: −0.06 vs. -0.03, p = .09; Breast: −0.03 vs. −0.04, p = .65; Lung: −0.07 vs. −0.07, p = .95); nor for Physical Component Summary or Mental Component Summary scores. Conclusion: Older patients treated for prostate, breast or lung cancer in the later era reported similar outcomes of changes in HRQOL compared to earlier era patients.